Urban Borderlines: Negotiating Spatial, Social, and Symbolic Boundaries in Urban Contexts. (27th October 2020) - Jalili, Jaleh
Abstract: Sociological research has productively engaged with boundary processes in urban contexts, but few studies explore the relation between space and social and symbolic boundaries. Based on fieldwork in Tehran, Iran, and building on literature on boundary processes, I incorporate a spatial approach into the discussion of social and symbolic boundaries. The focus is on city-level public spaces that function beyond neighborhoods and draw people from outside the immediate community. This article expands the discussion of boundaries beyond particular neighborhoods by situating social relations in the broader context of the metropolitan area. In Tehran, urban developments have increased mobility in use of public spaces, particularly enabling the less privileged in the south to move more easily and use spaces in the north, resulting in a fairly mixed social landscape. Using observations, survey data, and interviews with users of public spaces, I study the related social consequences and explore how boundaries are perceived and negotiated in changing urban environments. The findings shed light on some of the processes through which social and symbolic boundaries are questioned or maintained, as spatial boundaries become more fluid, blurred, and negotiable in a more accessible city.